2023
DOI: 10.1038/s43587-023-00449-3
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin accessibility dynamics of neurogenic niche cells reveal defects in neural stem cell adhesion and migration during aging

Abstract: The regenerative potential of brain stem cell niches deteriorates during aging. Yet the mechanisms underlying this decline are largely unknown. Here we characterize genome-wide chromatin accessibility of neurogenic niche cells in vivo during aging. Interestingly, chromatin accessibility at adhesion and migration genes decreases with age in quiescent neural stem cells (NSCs) but increases with age in activated (proliferative) NSCs. Quiescent and activated NSCs exhibit opposing adhesion behaviors during aging: q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 142 publications
2
5
0
Order By: Relevance
“…We found that NSC ingression into the scratch was slowed in SU5416-treated NSCs compared with control NSCs ( Fig 6C and D ). To test proliferative NSC adhesion, we used an attachment assay ( Yeo et al, 2023 ). After 24 h pretreatment with SU5416 (or vehicle DMSO), we treated NSCs in standard proliferative monolayer conditions with cell-permeable Hoechst dye to label nuclei then imaged the monolayers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that NSC ingression into the scratch was slowed in SU5416-treated NSCs compared with control NSCs ( Fig 6C and D ). To test proliferative NSC adhesion, we used an attachment assay ( Yeo et al, 2023 ). After 24 h pretreatment with SU5416 (or vehicle DMSO), we treated NSCs in standard proliferative monolayer conditions with cell-permeable Hoechst dye to label nuclei then imaged the monolayers.…”
Section: Resultsmentioning
confidence: 99%
“…In the SVZ, quiescent NSCs are relatively stationary, much like DG RGL-NSCs, and their proliferative progeny are highly motile, like DG IPCs. A recent study showed that the motility and cell adhesion properties of these SVZ cells are linked and can change with stimuli such as advancing age ( Yeo et al, 2023 ). Our in vitro motility and adhesion assays, coupled with our in vivo transcriptomics, align to suggest that adhesion and motility are promoted by autocrine VEGF signaling in adult DG NSCs.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has linked increased adhesion in proliferative neural stem cell niches to reduced proliferative potential, a process that naturally occurs during aging 29 . We performed a proteomic profiling of cortices from E15.5 i4F-Nes and their corresponding control litermates (CTR) after 4d of low Dox treatment (Fig 2F).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a recent study indicated that aging has a profound effect on the expression of genes involved in cell-cell adhesion and cell-matrix interactions in brain stem cell niches. Aging increases the cellular adhesion of proliferative neural stem cells, which correlates with reduced neurogenesis potential 29 . Accordingly, our results suggest that transient reprograming could also rejuvenate the niche of neuronal progenitors by reducing the expression of cell adhesion proteins, thereby increasing their neurogenesis capability.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, biomarkers have been developed to measure a variety of aging features, from molecular and cellular markers to organismal phenotypes. 3 For example, a number of hallmarks of aging, such as changes in transcriptional 4 8 and epigenetic networks, 9 12 loss of proteostasis, 13 15 stem cell dysfunction, 16 18 and frailty, 19 have all been used as metrics of aging.…”
Section: Introductionmentioning
confidence: 99%